2022
DOI: 10.3389/fpain.2022.991736
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and non-pharmacological therapeutic interventions for the treatment of spinal cord injury-induced pain

Abstract: Spinal cord injury (SCI) is a complex neurophysiological disorder, which can result in many long-term complications including changes in mobility, bowel and bladder function, cardiovascular function, and metabolism. In addition, most individuals with SCI experience some form of chronic pain, with one-third of these individuals rating their pain as severe and unrelenting. SCI-induced chronic pain is considered to be “high impact” and broadly affects a number of outcome measures, including daily activity, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 189 publications
0
10
0
Order By: Relevance
“…Our findings showed that general pain also impacted individuals’ desire to eat. Eller et al (2022) reported that most individuals with SCI/D have chronic pain, many of whom rate their pain as severe. As caloric and nutrition needs are altered after SCI/D and are often unmet, individuals may experience chronic inflammation which is a primary cause of pain after SCI/D (Eller et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings showed that general pain also impacted individuals’ desire to eat. Eller et al (2022) reported that most individuals with SCI/D have chronic pain, many of whom rate their pain as severe. As caloric and nutrition needs are altered after SCI/D and are often unmet, individuals may experience chronic inflammation which is a primary cause of pain after SCI/D (Eller et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Eller et al (2022) reported that most individuals with SCI/D have chronic pain, many of whom rate their pain as severe. As caloric and nutrition needs are altered after SCI/D and are often unmet, individuals may experience chronic inflammation which is a primary cause of pain after SCI/D (Eller et al, 2022). Dietary interventions, including anti-inflammatory diets, may be a promising strategy for long-term pain reduction in this population (Allison et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Moreover, when post-SCI pain becomes chronic, treatment becomes further difficult. 10 Replacing or supplementing traditional pharmacological approaches with nonpharmacological interventions may be a potential choice for improving patient outcomes for NP. 10,11 However, literature on exploring the mechanisms of nonpharmacological interventions remains lacking, limiting the development of effective treatments.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…10 Replacing or supplementing traditional pharmacological approaches with nonpharmacological interventions may be a potential choice for improving patient outcomes for NP. 10,11 However, literature on exploring the mechanisms of nonpharmacological interventions remains lacking, limiting the development of effective treatments. Photobiomodulation (PBM) is a treatment performed using very low energy light, which is sufficient to produce stimulation, but does not damage the target system.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation